Development of interactive media based on differentiated learning in front office subjects - Yusra Mardiali; Abna Hidayati; Zulhendri Zen; Alwen Bentri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The diversity of learning styles in vocational schools requires innovative and personalized instructional media. This study aimed to develop and evaluate a differentiated instruction-based interactive learning media for the Front Office subject at SMKN 1 Painan. Using a Research and Development design with the Four-D model (Define, Design, Develop, Disseminate), the study involved curriculum analysis, learner profiling, prototype development via Google Sites, expert validation (five validators), and practicality testing with 30 students and three teachers. Data were collected through pretest-posttest scores, Likert-scale questionnaires, and thematic feedback. Results showed high validity (92–98%), good practicality (90–95%), and a 24% average improvement in student learning outcomes, demonstrating initial effectiveness. Multimedia integration and differentiated features allowed students to learn according to their style and pace, while alignment with the Merdeka Curriculum ensured competency achievement in Front Office skills. The media was positively received by teachers and students, indicating its potential for broader implementation in vocational education.